NEWLY FOUND MIDDLE PERSIAN INSCRIPTIONS OF ĀMĀRGAR DARIUŠ IN DERBENT - Gadziev, Murtazali Serazutdinovic; Duncov, Aleksej Nikolaevic (History, Archeology and Ethnography of the Caucasus, 2023)
Until recently, 32 Middle Persian inscriptions documenting the construction of the Derbent defensive complex and dating from the very end of the 560s. AD were known. Now the construction Middle Persian inscriptions of Derbent has been replenished with two more inscriptions - No. 33 and No. 34, opened by the authors in 2016 and 2021, respectively. Inscription No. 33 is located between towers 18 and 19 of the northern city defensive wall in the central part of the curtain, at a height of 1.5 m. It has poor preservation. But, nevertheless, its text is restored from the preserved fragments of letters and by analogy with other inscriptions similar in content. The inscription is three-line, vertical. Reconstructible text: [Da]r[iuš ī] Ā[durbādagān] ām[ārgar]. Inscription No. 34 is located between towers 14 and 15 of the northern wall, at a height of 2.15-2.6 m. The inscription is vertical, three-line, separate letters and parts of letters are preserved, and its text is reconstructed according to the surviving letters and analogies with other inscriptions. Its text reads: Dari[u]š ī [Ādurbādag]ān ām[ā]rgar.Both inscriptions are composed on behalf of the āmārgar – a high official, chief financier and tax inspector of the vast Adurbadagan area, which during the reign of Shahanshah Khosrow I Anushirvan (531-579) included not only Adurbadagan proper, but all the Caucasian possessions of Sasanian Iran up to Derbent. The newly discovered inscriptions No. 33 and No. 34 belong to the subgroup b, group 1 of the Middle Persian inscriptions of Derbent, which represents the inscriptions of āmārgar Dariush. Now 19 (out of 34) inscriptions compiled on his behalf are already known, and all of them are carved on the northern wall of the city, where a total of 24 inscriptions are located.
Keywords: Derbent; Sasanian Iran; Middle Persian inscriptions; Dariuš; āmārgar; Ādurbādagān